(untitled) (Research, Society and Development, 2021)
Objective: This article aimed to measure the quality of life of substance users who were undergoing treatment at a psychosocial care service specialized in alcohol and other drugs. Methodology: this is a cross-sectional, descriptive study with a quantitative approach, carried out with the participation of 100 users who were undergoing treatment at the service. Empirical data were collected between July and August 2017 using the WHOQOL-BREF instrument in the social relations domain. Results: the quality of life had a mean score of 62.67 and a median of 63.5. Socioeconomic factors such as education, occupation, housing conditions, family ties and income were significant elements in determining quality of life. Conclusion: the results pointed to a quality of life considered moderate. The care modalities offered by psychosocial care services for alcohol and other drugs seem to converge with the multifactorial sense of quality of life as it works with a plurality of dimensions of the users’ lives.